CRM1 Is a Direct Cellular Target of the Natural Anti-cancer Agent Plumbagin - Xuejiao Liu; Mingshan Niu; Xiaoyu Xu; Wei Cai; Lingyu Zeng; Xiuping Zhou; Rutong Yu; Kailin Xu (Elsevier, 2014)
Plumbagin, a naphthoquinone derived from the medicinal plant Plumbago zeylanica, has been shown to exert anti-cancer and anti-proliferative activities in vitro as well as in animal tumor models. However, the mechanism underlying its anti-tumor action still remains unclear. CRM1 is a nuclear export receptor involved in the active transport of tumor suppressors whose function is altered in cancer due to increased expression and overactive transport. We showed that CRM1 is a direct cellular target of plumbagin. The nuclei of cells incubated with plumbagin accumulated tumor-suppressor proteins and inhibited the interactions between CRM1 and these proteins. Particularly, we demonstrated that plumbagin could specifically react with the conserved Cys528 of CRM1 but not with a Cys528 mutant peptide through Mass spectrometric analysis. More importantly, cancer cells that are transfected with mutant CRM1 (C528S) are resistant to the inhibitory effects of plumbagin, demonstrating that the inhibition is through direct interaction with Cys528 of CRM1. The inhibition of nuclear traffic by plumbagin may account for its therapeutic properties in cancer and inflammatory diseases. Our findings could contribute to the development of a new class of CRM1 inhibitors. Keywords:: plumbagin, CRM1, nuclear protein export, anti-tumor